2012
DOI: 10.1007/s11107-011-0370-7
|View full text |Cite
|
Sign up to set email alerts
|

Power consumption modeling in optical multilayer networks

Abstract: -The evaluation and reduction of energy consumption of backbone telecommunication networks has been a popular subject of academic research for the last decade. A critical parameter in these studies is the power consumption of the individual network devices. It appears that across different studies, a wide range of power values for similar equipment is used. This is a result of the scattered and limited availability of power values for optical multilayer network equipment. We propose reference power consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
157
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(158 citation statements)
references
References 12 publications
1
157
0
Order By: Relevance
“…[3], instead of the bottom-up approach outlined above for evaluating novel power saving techniques. This paper uses a top-down power model to survey opportunities for reducing power consumption -Our earlier work [4] was a response to the issue outlined above where representative power consumption values are hard to obtain. We presented best-effort power consumption reference values for the main building blocks of backbone network equipment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3], instead of the bottom-up approach outlined above for evaluating novel power saving techniques. This paper uses a top-down power model to survey opportunities for reducing power consumption -Our earlier work [4] was a response to the issue outlined above where representative power consumption values are hard to obtain. We presented best-effort power consumption reference values for the main building blocks of backbone network equipment.…”
Section: Introductionmentioning
confidence: 99%
“…For the remainder of this paper, we first briefly summarize the analytical power model from [4] in Section II, before using this model in Section III to discuss a number of power reduction approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Constraint (16) ensures that the number of wavelengths in a physical link does not exceed the capacity of fibers in the physical links. Constraint (17) gives the total number of wavelength channels used in a physical link.…”
Section: Link Embedding Constraintsmentioning
confidence: 99%
“…3 shows the overall non-renewable power consumption and solar power consumption of the GVNE model at different times of the day. It can be observed that despite having an increase in the CPU cores and bandwidth demand between 06:00 hours and 12:00 Table II: Parameters used in the model Distance between two neighboring EDFAs (S) [16] 80 (km) Distance between two neighboring Regenerators (RG) [17] 2000 (km) Number of wavelengths in a fiber (W) [18] 32 Wavelength Rate (B) 40Gbps Power consumption of a transponder (PT) [16] 167 (W) Power consumption of a regenerator (RG) [19] 334 (W) Power consumption of a 40Gb/s router port (PR) [17] 850(W) Power consumption of an EDFA (PE) [16] 55 (W) Power consumption per CPU core [20] 11.25 (W) hours, the non-renewable power consumption continues to decrease as expected due to the increasing availability of solar power. In order to adequately serve the further increase in load from the VNRs, there is a subtle increase in non-renewable power consumption from 14:00 hours until 20:00 hours and thereafter, there is a sharp increase in nonrenewable power consumption due to the dwindling solar energy supply during this period.…”
Section: Link Embedding Constraintsmentioning
confidence: 99%
“…The per-port power values for 10 Gbps and 100 Gbps electronic Ethernet interfaces are taken from [10] and they are considered to be independent of the load. The WSS power consumption value has been taken from [11].…”
Section: Performance Evaluationmentioning
confidence: 99%